Innovation policies in Uzbekistan: Path taken by ZEFa project on innovations in the sphere of agriculture - Rano Turaeva (University of Bonn, Center for Development Research (ZEF), 2012)
The paper describes the existing mechanisms of innovation diffusion particularly focusing on the initial phase to introduce the results of innovative projects into the government system of Uzbekistan. The paper aims to analyze the existing bureaucratic, legal and political matrix for the introduction of ZEF project innovations into practice. The innovations developed by the staff of the ZEF/UNESCO project in Uzbekistan range from their content and purpose of use from technological to institutional ones. The innovations considered in this paper are mainly technological ones. The analysis will be supported by two other examples of innovation diffusion by international projects in Uzbekistan. Based on the theoretical analysis of my empirical data I argue that a functioning innovation system is on the way to be developed to completely function in Uzbekistan. There is rather knowledge ecology to use Foray's term which could further serve as a basis for the future innovation system. This argument is substantiated by empirical study of our project innovations and their individual paths to their diffusion detailed in this paper.
Keywords: 330; Land Politics; Innovation; Agricultural Politics in Uzbekistan; State; Central Asia